MicroRNA‐132 suppresses migration and invasion of renal carcinoma cells. Issue 1 (17th October 2019) - Yu, Yi; Lu, Wenbao; Zhou, Xinmin; Huang, Hua; Shen, Shaochen; Guo, Lian
Abstract: Background: The aim of this study was to explain the effects of microRNA‐132 in renal cell carcinoma by regulating FOXM1 expression. Methods: Thirty patients with renal cell carcinoma admitted to our hospital were enrolled, and their adjacent normal tissues and cancer tissues were taken. The expression of microRNA‐132 was measured by in situ hybridization (ISH) and RT‐PCR, and the expression of FOXM1 was evaluated by RT‐PCR and immunohistochemistry (IHC), and the correlation between microRNA‐132 and FOXM1 was analyzed. In the cell experiment, the KETR‐3 cells were divided into three groups: Negative control (NC) group were treated with nothing; blank (BL) group were transfected with empty vector; and microRNA‐132 (miRNA) group were transfected with microRNA‐132. The cell invasion and migration abilities among groups were assessed by transwell and wound healing assays. The expression levels of related proteins (FOXM1, MMP‐2, MMP‐9, VEGF‐alpha, and uPAR) were determined by Western blot. Results: Depending on clinical data, we found that FOXM1 protein expression of renal cell carcinoma tissues was higher than that in adjacent normal tissues. MiRNA‐132 was negative correlation with FOXM1. In vitro, the number of invasive cells and wound healing rate in the microRNA group were significantly suppressed than those in the NC group ( P < 0.05, respectively). In the Western blot assay, the results showed that the protein expression levels of FOXM1, MMP‐2, MMP‐9, VEGF‐α, and uPAR were significantly inhibited in the miRNA group compared with the NC group ( P < 0.05, respectively). Conclusion: miRNA‐132 had anti‐tumor effects in renal cell carcinoma by suppressing FOXM1 expression.